Inflammatory Cytokines Correlate with Dry Eye Indexes Estimated by Keratograph in Healthy Subjects - Fahmy, Rania; Al-Muammar, May N.; Alonazi, Mona; Bhat, Ramesa S.; El-Ansary, Afaf (Current Proteomics, 2021)
Background: Inflammation plays a major role in dry eye diseases and is the prime target in clinical treatments of the disease. Objective: To determine whether the inflammatory cytokines in the tear film of patients with dry eye correlate with parameters such as Tear Break-Up Time (TBUT) and Tear Meniscus Height (TMH) and could be used together as predictive biomarkers of disease severity. Methods: This study included 58 eyes (29 female subjects; age, 19–25 years) comprising 20 normal eyes (control), 20 eyes (level 1 dryness), and 18 eyes (level 2 dryness). Dryness level 1 or 2 is keratographic diagnosis according to the tear break-up time cut-off value obtained. After ophthalmic examinations, including determination of non-invasive TBUT average and first second and TMH using Keratograph 4 (to measure dryness level), tears of all participants were collected. Five cytokines, including interleukin 6, 10, 12, interferon-γ, and tumor necrosis factor-α, were measured using ELISA. Results: Significant changes were observed in all measured cytokines and these changes correlated with eye dryness severity scores. Both groups (levels 1 & 2) showed remarkable changes related to ocular surface alterations in clinical examinations. Significantly, shorter TBUT and TMH were recorded in both groups and were positively correlated with the dryness severity. Conclusion: Cytokines could be used as predictive markers for pre-clinical diagnosis of dry eye diseases and as prognostic markers to monitor treatment effectiveness.
Keywords: non-invasive